1995
DOI: 10.1128/aac.39.7.1546
|View full text |Cite
|
Sign up to set email alerts
|

Valaciclovir compared with acyclovir for improved therapy for herpes zoster in immunocompetent adults

Abstract: Acyclovir treatment of acute herpes zoster speeds rash healing and decreases pain and ocular complications. The limited oral bioavailability of acyclovir necessitates frequent dosing. Valaciclovir, the l-valyl ester of acyclovir, is rapidly and almost completely converted to acyclovir in vivo and gives three-to fivefold increases in acyclovir bioavailability. In a randomized, double-blind, multicenter study, the safety and efficacy of oral valaciclovir given at a dosage of 1,000 mg three times daily for 7 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
294
3
18

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 561 publications
(324 citation statements)
references
References 21 publications
9
294
3
18
Order By: Relevance
“…Five papers which reported the results of antiviral trials of herpes zoster were reviewed by the participants (Degreef and the Famciclovir Herpes Zoster Clinical Study Group, 1994;Beutner et al, 1995;Tyring et al, 1995;Wood et al, 1994Wood et al, , 1996. The research designs, methods of data analysis, and results of these trials were systematically examined, in order to provide a basis for a comprehensive examination of the analysis of prolonged pain in herpes zoster trials.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five papers which reported the results of antiviral trials of herpes zoster were reviewed by the participants (Degreef and the Famciclovir Herpes Zoster Clinical Study Group, 1994;Beutner et al, 1995;Tyring et al, 1995;Wood et al, 1994Wood et al, , 1996. The research designs, methods of data analysis, and results of these trials were systematically examined, in order to provide a basis for a comprehensive examination of the analysis of prolonged pain in herpes zoster trials.…”
Section: Methodsmentioning
confidence: 99%
“…Covariate analyses are valuable for examining factors that predict prolonged pain and better therapeutic response; for pivotal trials, however, such analyses should be few in number and prospectively identified, with adjustments made for multiple comparisons if necessary. Older age and greater pain severity at enrollment have been found to be associated with prolonged herpes zoster pain in a large number of studies (e.g., McKendrick et al, 1994;Boon and Griffin, 1995;Beutner et al, 1995;Dworkin et al, 1995bDworkin et al, , 1996Whitley et al, 1996;Wood et al, 1996). Because of these robust associations, these two factors should be examined in all studies of herpes zoster and PHN.…”
Section: Should Adjustments Be Made For Covariates?mentioning
confidence: 99%
See 3 more Smart Citations